Establishing a Surgical Procedure for Rhesus Epiretinal Scaffold Implantation with HiPSC-Derived Retinal Progenitors - Ziming Luo; Kang Li; Kaijing Li; Bikun Xian; Ying Liu; Sijing Yang; Chaochao Xu; Zhigang Fan; Shoutao Lu; Haijun Zhang; Jian Ge (Stem Cells International)
Background. To develop an effective surgical procedure for cellular scaffold epiretinal implantation in rhesus, facilitating subsequent epiretinal stem cell transplantation. Methods. Retinal progenitors were seeded onto a poly(lactic-co-glycolic) acid (PLGA) scaffold. First, the cellular scaffolds were delivered by 18G catheter or retinal forceps into rabbit epiretinal space (n=50). Then, the cell survival rate was evaluated by Cell Counting Kit-8 (CCK-8). Second, three methods of scaffold fixation, including adhesion after gas-liquid exchange (n=1), tamponade by hydrogel (n=1), and fixation by retinal tacks (n=4), were performed in rhesus monkeys. After one month, fundus photography and SD-OCT were performed to assess the outcomes, and histological examination was performed to evaluate proliferation. Results. The cell survival rate was significantly higher in the catheter group. Follow-up examination showed that retinal tack fixation was the only method to maintain the scaffolds attached to host retina for at least 3 weeks, which is the minimal time required for cell integration. Histological staining demonstrated slight glial fibrillary acidic protein (GFAP) accumulation in the retinal tack insertion area. Conclusions. The established surgical procedure offers a new insight into research of epiretinal cell replacement therapy in rhesus eyes. The successful delivery and long-term fixation provide a prerequisite for cell migration and integration.